P075 Inflammatory Bowel Diseases and Autoimmune Hepatitis: Is Anti-TNF Therapy an Option?. (December 2019) - Rocha, Beatriz; Queiroz, Natália; Azevedo, Matheus; Alexandre, Carlos; Milani, Luciane; Cançado, Eduardo; Terrabuio, Debora; Barros, Luísa; Oba, Jane; Leite, André; Sipahi, Aytan; Damião, Adérson
Abstract : BACKGROUND: Comorbidities among immune mediated inflammatory disorders are frequently reported (1 ). Although some physicians are not aware of the potential association between autoimmune hepatitis (AIH) and inflammatory bowel diseases (IBD) it is not uncommon (2 ). As anti-tumor necrosis factor (anti-TNF) therapy has the potential to induce autoimmunity, including AIH (3 ), the safety of its utilization in this condition is unknown and often avoided by physicians. METHODS: Data from patients with concomitant diagnosis of IBD and AIH in the IBD unit of the Department of Gastroenterology of the Clinics Hospital of University of São Paulo was retrospectively collected based on medical records. RESULTS: Two female (29 and 33 years old) and one male (29 years old) patients with concomitant AIH and ulcerative colitis (pancolitis) were identified. These three patients needed to start infliximab because of persistent clinical and endoscopic activity in two of them and gangrenous pyoderma in the other case. All of them were taking azathioprine when anti-TNF was initiated. Two had type 1 AIH and one AIH with no markers. Two were cirrhotic (Child A/MELD 11 and Child B/MELD 14) with portal hypertension and one did not have signs and symptoms of cirrhosis. After a follow up of an average of 20 months under anti-TNF treatment transaminases slightly reduced (mean ALT prior treatment 50 ± 32 U/L, mean ALT during treatment 27 ± 8 U/L) and immunoglobulin G level slightly increased (pretreatment mean 2062 ± 626 mg/dL, mean during treatment 2595 ± 1158 mg/dL). Clinically, cirrhotic patients persisted with compensated liver disease (Child A / MELD 11 and Child B / MELD 15) and the one who was not cirrhotic did not have any clinical deterioration. After 19 months with anti-TNF the patient with MELD 15 (blood type B) was successfully submitted to liver transplantation and infliximab was discontinued after that. It is important to emphasize that MELD before and after anti-TNF in this case was almost the same. After 3 years, the patient with gangrenous pyoderma reactivated the skin lesions due to poor adherence to infliximab treatment, progressing to infectious complications and subsequent death. CONCLUSION(S): Anti-TNF do not seem to alter the course of liver disease in IBD patients with concomitant diagnosis of AIH. Due to potential side effects it needs to be applied with caution and in a multidisciplinary approach in tertiary centers with special attention to infectious complications.